Critical Illness Polyneuromyopathy Developing After Diabetic Ketoacidosis in an Intensive Care Unit - Mehmet Salih Sevdi; Meltem Turkay; Tolga Totoz; Serdar Demirgan; Melahat Karatmanlı Erol; Ali Özalp; Kerem Erkalp; Ayşin Alagöl (Galenos Yayinevi, 2015)
Critical illness polyneuromyopathy (CIPNM) is a primary axonal-degenerative condition that occurs in sensory and motor fibers after the onset of a critical illness. It is thought that it develops due to tissue damage due to hypoxia/ischemia. When 24-year-old female patient was followed in the intensive care unit (ICU) due to diabetic ketoacidosis, she was extubated on the second day. She was reintubated on the third day because of respiratory acidosis. Sedation was withdrawn on the fifth day, however the patient could not recover consciousness until the 14th day and tetraplegia was found during her neurological examination. Motor peripheral nerve-transmission response in the upper-and lower-extremity was evaluated to be of low amplitude in the conducted needle electroneuromyography. The patient was weaned from mechanical ventilation on the 23rd day. The neuromuscular symptoms developing as a result of critical illnesses reflect themselves as an increase in the hospitalization duration in the ICU, a difficulty in separation from the mechanical ventilator and an extension of rehabilitation.